Case report: Safety and efficacy of voxelotor in a patient with sickle cell disease and stage IV chronic kidney disease - Alshurafa, Awni; Yassin, Mohamed A. (Frontiers in Medicine, 2022)
Sickle cell disease (SCD) is a heterogeneous group of inherited disorders characterized by the production of sickle hemoglobin which is less soluble than an adult or fetal hemoglobin. Voxelotor is a hemoglobin S polymerization inhibitor that has been approved for sickle cell disease treatment in the adult and adolescent population. It acts as a hemoglobin modulator by increasing its affinity to oxygen which prevents red blood cells from sickling. Chronic kidney disease is a common but under-reported complication of SCD and it’s a leading cause of morbidity and mortality. The data about the safety and efficacy of Voxelotor use in chronic kidney disease is limited. Herein we report a 49-year-old gentleman, a known case of sickle cell disease and stage IV chronic kidney disease, who was managed successfully with Voxelotor and resulted in decreasing transfusion requirement and vaso-occlusive painful crisis without affecting kidney function.